Evidence for the Biosynthesis of Bryostatins by the Bacterial Symbiont “Candidatus Endobugula sertula” of the Bryozoan Bugula neritina - Davidson, S. K. (American Society for Microbiology, 2001)
The marine bryozoan, Bugula neritina, is the source of the bryostatins, a family of macrocyclic lactones with anticancer activity. Bryostatins have long been suspected to be bacterial products. B. neritina harbors the uncultivated gamma proteobacterial symbiont “Candidatus Endobugula sertula.” In this work several lines of evidence are presented that show that the symbiont is the most likely source of bryostatins. Bryostatins are complex polyketides similar to bacterial secondary metabolites synthesized by modular type I polyketide synthases (PKS-I). PKS-I gene fragments were cloned from DNA extracted from the B. neritina-“E. sertula” association, and then primers specific to one of these clones, KSa, were shown to amplify the KSa gene specifically and universally from total B. neritina DNA. In addition, a KSa RNA probe was shown to bind specifically to the symbiotic bacteria located in the pallial sinus of the larvae of B. neritina and not to B. neritina cells or to other bacteria. Finally, B. neritina colonies grown in the laboratory were treated with antibiotics to reduce the numbers of bacterial symbionts. Decreased symbiont levels resulted in the reduction of the KSa signal as well as the bryostatin content. These data provide evidence that the symbiont E. sertula has the genetic potential to make bryostatins and is necessary in full complement for the host bryozoan to produce normal levels of bryostatins. This study demonstrates that it may be possible to clone bryostatin genes from B. neritina directly and use these to produce bryostatins in heterologous host bacteria.